Effect of Problem-based Learning versus Role Play on Knowledge of Managing Aggressive Patient among Staff Nurses in a selected Hospital in Kolkata - Malik, Kakali (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of the study is to evaluate the problem-based learning’s (PBL) efficacy versus role play (RP) on the knowledge of managing aggressive patients among staff nurses. Introduction: Managing aggressive patients is critical in health-care settings, necessitating effective training methods to enhance nurses’ skills. The study is grounded in the system model of Theorist Ludwig Von Bertalanffy. Materials and Methods: A non-equivalent pre- and post-test design was used utilizing purposive sampling of sixty nursing staff. Samples were given a validated and reliable (r = 0.89) knowledge questionnaire. Following the pre-test, PBL was introduced first group and RP to the other. Post-test was conducted on the 8th day. Paired “t” tests compared each group’s pre- and post-test results. Results: Both PBL and RP effectively enhanced knowledge. The value of paired “t” for the PBL group was 37.57 [t(29) = 2.05; P < 0.05], improving from a pre-test mean of 11.1–19.8 post-test. The RP group’s paired “t” value was 25.04 [t(29) = 2.05; P < 0.05], improving from 10.6 to 17.6. An unpaired “t” test showed that PBL was more effective than RP, with a “t” value of 4.67 [t(58) = 2.00; P < 0.05]. There was no significant association between pre-test scores and demographic variables. Conclusion: PBL was superior to RP in improving staff nurses’ knowledge of managing aggressive patients. Future research should explore PBL in clinical settings and other educational methods alongside PBL and RP.